Psychosocial risk among shift workers in food and beverages industry in Kuala Lumpur - Husni, Nurhafizah (2023)
As the world begins to provide 24-hour services in many industries to meet the continuous demand of the urban world, workers have become accustomed to working on shift schedules. Shift work entails working on a regular or rotating schedule, such as in the morning, evening, or night. Shift work not only causes occupational stress for employees, but it also has an impact on individuals' physical and psychological wellbeing and work performance due to circadian rhythm disruption. Working in shifts has caused biological clocks to shift, reducing individuals' performance efficiency and jeopardizing any potential economic benefits. Many studies have looked into the effects of shift work on physical health, but little attention has been paid to shift workers' mental health. The purpose of this study is to investigate shift workers' psychosocial status and risk factors. Shift workers (n = 165) were chosen at random to complete questionnaires about LEOs and DASS-21. It was discovered that the working environment and work status influenced the likelihood of employees experiencing mental health illnesses due to stress, anxiety and depression. More research is needed to better understand the effects of shift work on employee mental health.